Bioakumulasi kadmium (Cd), timbal (Pb), dan tembaga (Cu) pada gastropoda di Desa Kersik, Kabupaten Kutai Kartanegara, Kalimantan Timur: Bioaccumulation of Cadmium (Cd), Lead (Pb), and Cadmium (Cu) in Gastropods in Kersik Village, Kutai Kartanegara Regency, East Kalimantan - Muslim, Izza Dzikriyah; Rafii, Akhmad; Ghitarina, Ghitarina (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
Heavy metals are compounds that can affect the quality of a waters. Various kinds and types of heavy metals that enter and settle in sediments can cause diversity to decrease to the extinction of organisms in the waters. This study was aimed to determine the content of Cd, Pb, and Cu accumulated in water, substrate, and gastropods obtained from Kersik Village, Kutai Kartanegara Regency, East Kalimantan. Samples of water, substrate, and gastropods were collected from 4 stations with 3 repetitions. Water samples, substrates, and gastropods were analyzed using AAS. Concentration ranges of Cd, Pb, and Cu in water were 0.003 - 0.011 mg/L; 0.161 - 0.731 mg/L; and 0.007 - 0.009 mg/L, respectively. The concentration ranges of Cd, Pb, and Cu on the substrate were 0.021 - 0.182 mg/kg; 19.5 - 31.12 mg/kg; and 14.29 - 15.47 mg/kg, respectively. In gastropods, the range of Cd concentrations was 0.509 - 0.675 mg/kg, while for Pb and Cu were 15.96 - 21.52 mg/kg and 57.78 - 92.4 mg/kg, respectively. The concentration of Pb in gastropods at all stations has exceeded the quality standard based on SNI-7387-2009, while the concentration of Cu in gastropods at all stations has also exceeded the quality standard based on BPOM No.03725/B/SK/89. Bioconcentration Factor (BCF) of organisms to sediment (BCFo-s), shows the ability to accumulate Cu in Gastropods which is higher than Cd and Pb. Bioconcentration Factor (BCF) analysis of organisms to water (BCFo-w), showed that the accumulation of Cd, Pb, and Cu were in the low, medium, to high categories. The average comparison of concentrations of the three heavy metals at each observation station was not significantly different (sig. > 0.05).